Media Sosial dan Pembentukan Opini Publik (Analisis Studi Kasus Echo Chamber Pada Interaksi Komentar di Akun Instagram @Turnbackhoaxid Dalam Konteks Post – Truth) - Alfifa, Astika Nisa; Batubara, Viandra Fahira Ramadani; Sakinah, Khairani; Manik, Jahirun; Yoes, Rifqi Adriansa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The spread of false information or hoaxes on social media is increasingly becoming a serious problem that disrupts public trust and causes confusion. The role of social media in the formation of public opinion in the era of globalization is marked by advances in communication technology. With the increasing access to information, social media has become the main platform for individuals and groups to express their opinions and interact. This study examines the influence of social media on public opinion, including the pattern of comment interaction that occurs on the platform, focusing on @turnbackhoaxid accounts as a case study. This study seeks to understand how social media, as the dominant communication platform, influences the way individuals and groups express their opinions and interact with each other. This study also examines the interaction patterns of comments on certain social media accounts, such as @turnbackhoaxid, to identify the dynamics that occur in public discussions, especially in the context of the post-truth and echo chamber phenomenon. This research emphasizes the importance of digital literacy in combating hoaxes and misinformation. Therefore, this study suggests the need for more effective educational strategies to improve the ability of individuals to critically assess information in facing challenges in the post-truth era.